2018
DOI: 10.14474/ptrs.2018.7.2.83
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of characteristics during backward walking according to various stride frequencies in underwater and ground environments

Abstract: Objective:The purpose of this study was to investigate the relationship between heart rate (HR), self-awareness of exercise intensity (rating of perceived exertion, RPE), and 5-meter walk test (5MWT) of persons affected by stroke during backward walking according to the preferred stride frequency (PSF), PSF+3 and PSF+6 conditions. Design: Cross-sectional study. Methods: A total of 11 persons with stroke (9 males, 2 females) participated voluntarily. All patients underwent backward walking under the PSF, PSF+3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…9 For these reasons, underwater exercise is often recommended for elderly patients and stroke patients in order to cope with pathological pain in general. 7,[10][11][12][13] In recent years, studies focusing on underwater gait have been conducted and reported results including the improvement in muscle activity, heart rate, maximal oxygen uptake, stance stability, and symmetry through underwater gait. [14][15][16][17][18][19][20][21][22] However, in most studies, there were no interventions regarding gait velocity in water.…”
Section: J Kptmentioning
confidence: 99%
“…9 For these reasons, underwater exercise is often recommended for elderly patients and stroke patients in order to cope with pathological pain in general. 7,[10][11][12][13] In recent years, studies focusing on underwater gait have been conducted and reported results including the improvement in muscle activity, heart rate, maximal oxygen uptake, stance stability, and symmetry through underwater gait. [14][15][16][17][18][19][20][21][22] However, in most studies, there were no interventions regarding gait velocity in water.…”
Section: J Kptmentioning
confidence: 99%